PENGARUH KUALITAS PELAYANAN, HARGA DAN LOKASI TERHADAP KEPUASAN KONSUMEN (Studi Kasus Pada Konsumen Rolag Kopi Karah Surabaya) - Sari, Nindi; Maruta, IGN Anom; Mulyati, Awin (Jurnal Dinamika Administrasi Bisnis, 2020)
ABSTRACT In this era of globalization, there have been many cafes that have sprung up in all countries, such as in Indonesia especially in Surabaya, we have found many cafes everywhere. The words cafe comes from French which means coffee drinks, over time the cafe not only provides coffee but also provides foods such as snacks, appetizers, main course until the desserts. Karah Coffee Rolag Surabaya is a place of this research. The purpose of this study is to find out how much service quality, price, and location influence on customer satisfaction.This type of research is quantitative research. The study population was consumers of Karah Kopi Rolag Surabaya. While the sample of 100 respondents using the non-probability method (non-random sampling) and data collection using a questionnaire. The data analysis technique used in this study is a multiple linear regression analysis. The results of this study show that the quality of service, price, and location have a strong related influence on consumer satisfaction in Rolag Kopi Karah Surabaya. Based on the conclusion, it is expected that Rolag Kopi Karah Surabaya can further increase the variable Service Quality, Price, and Location of Consumer Satisfaction in order to maintain both consumers and customers.Keywords: service quality, price, location, and customer satisfaction.